2016
DOI: 10.1016/j.drugalcdep.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Hair analysis and its concordance with self-report for drug users presenting in emergency department

Abstract: Background Secondary analysis using data from the National Drug Abuse Treatment Clinical Trials Network randomized trial (NCT # 01207791), in which 1,285 adult ED patients endorsing moderate to severe problems related to drug use were recruited from 6 US academic hospitals. Objective To investigate the utility of hair analysis in drug use disorder trials with infrequent visits, and its concordance with Timeline Follow Back (TLFB). Methods This study compared the self-reported drug use on the TLFB instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Although Black participants with SUDs overall had greater odds of providing a hair sample relative to their White counterparts, Black participants reporting prescription opioid dependence with positive hair samples had greater odds of underreporting use compared to their White counterparts. However, Black participants using prescription and street opioid drugs were less likely to overreport use given a negative hair sample than Whites (Sharma, Oden, VanVeldhuisen, & Bogenschutz, 2016). As consistent with other studies (Feucht, Stephens, & Walker, 1994; Ledgerwood, Goldberger, Risk, Lewis, & Price, 2008), these findings suggest that the rates of disagreement between self-report and hair test results are higher among Black individuals and often varies by drug type.…”
Section: Resultsmentioning
confidence: 99%
“…Although Black participants with SUDs overall had greater odds of providing a hair sample relative to their White counterparts, Black participants reporting prescription opioid dependence with positive hair samples had greater odds of underreporting use compared to their White counterparts. However, Black participants using prescription and street opioid drugs were less likely to overreport use given a negative hair sample than Whites (Sharma, Oden, VanVeldhuisen, & Bogenschutz, 2016). As consistent with other studies (Feucht, Stephens, & Walker, 1994; Ledgerwood, Goldberger, Risk, Lewis, & Price, 2008), these findings suggest that the rates of disagreement between self-report and hair test results are higher among Black individuals and often varies by drug type.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, urine testing was able to validate over 50% more instances of reported marijuana use than hair testing. Several other studies have also reported low sensitivity in detecting marijuana and/or lower concordance between hair test results and self-reported marijuana use (Gryczynski et al, 2014;Ledgerwood et al, 2008;Musshoff et al, 2006), though Sharma et al (2016) reported 93% agreement between self-reported marijuana use and hair tests (utilizing 90-day window periods). One potential explanation is that infrequent marijuana use (e.g., weekly use or less) is more difficult to detect in hair (Taylor et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, although recall for cannabis is best for the past 30 days, the test–retest reliability of 6‐ and 12‐month recall periods are also excellent 46,48 . A number of studies have validated self‐reports of substance use and show high concordance between self‐reports of cannabis use as compared with toxicology results 49,50 . Together this, along with data that shows self‐reports of substance use have high concordance with toxicology results suggests that although there may be bias resulting from the way in which cannabis use is assessed, the EHR assessment favors those who are recent and more regular cannabis users.…”
Section: Discussionmentioning
confidence: 99%